Rethinking Responses to Political Crisis and Collapse: Hannah Arendt, Edith Stein, Rosa Luxemburg, and Simone Weil., King’s College, London ON, Canada, 6th – 8th March 2020 - Robaszkiewicz, Maria (HannahArendt.net, 2021)
--